(untitled) (Research, Society and Development, 2022)
The objective of this literature review was to identify publications on Relational Psychomotricity in Brazil. For this, a search of scientific material was carried out in the Google Scholar, Scielo, Pubmed and Birene databases, published between 2002 and 2022, in addition to books sold on the Amazon, Buscapé and Saraiva websites in Portuguese. The descriptors used as keywords were: Relational Psychomotricity. When searching for scientific articles, no work was found in Pubmed and Scielo; a single article was discovered in Birene and this same article was found repeated in Google academic, which contains approximately 5,890 works; however, of these, 08 (eight) are paid without free access, 31 published in monograph-type repositories; 61 published in events, seminars, abstracts, 02 (two) e-books, 36 repeated files or only in citation form; and 5728 incomplete files and without the keyword used. It was concluded that the theme of Relational Psychomotricity, within the literature found, is an important methodology in child development and other stages of human life, bringing mechanical, cognitive and affective benefits, given that, through Relational Psychomotricity, the human being finds a possibility to re-signify present processes, conscious or unconscious, in their life trajectory, in order to symbolically relive situations, to express from their most intimate feelings to an externalization of their emotions, joys and fears, making life healthier in all relationships with oneself, with the family and with society.